2016
DOI: 10.1159/000448433
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index Monitoring Reduces the Dosage of Propofol and Adverse Events in Sedation for Endobronchial Ultrasound

Abstract: Background: Current guidelines recommend monitoring the anesthetic depth of sedation during respiratory endoscopy by using clinical scales despite their subjective nature and the potential change in the level of sedation caused by frequent stimulation. Monitoring by means of the bispectral index (BIS) has shown its utility in reducing the use of drugs and their adverse events in general anesthesia, but evidence in prolonged sedation is insufficient. Objective: Our objective was to evaluate BIS in patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
3
13
2
Order By: Relevance
“…The MA group demonstrated significantly less AUC Desat , while decreasing airway obstruction and hypoxic events. The percentage of patients using the standard bite block with airway obstruction and hypoxic events was compatible with previous studies of 60~95% and 47~80%, respectively [8, 9, 30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The MA group demonstrated significantly less AUC Desat , while decreasing airway obstruction and hypoxic events. The percentage of patients using the standard bite block with airway obstruction and hypoxic events was compatible with previous studies of 60~95% and 47~80%, respectively [8, 9, 30].…”
Section: Discussionsupporting
confidence: 91%
“…Sedation using common medications such as midazolam, opioids, and propofol causes respiratory depression, hypoventilation, and subsequent hypoxemia [7]. Airway management is crucial during deep sedation, since desaturation is noted in up to 60% of patients [8] and as high as 95% of patients have different degrees of airway obstruction [9]. During deep sedation, the laryngeal muscle loses tone, causing partial or complete upper airway obstruction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, higher incidence or longer duration of burst suppression are significantly associated with the incidence of POD [ 55 , 56 ]. On the other hand, the use of EEG monitoring also reduced the dosage of general anesthetics, such as volatile agents and propofol [ 57 , 58 ]. Previous studies have reported that excessively exposure to potent volatile agents might increase the incidence of POD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high incidence or longer duration of burst suppression are significantly associated with the incidence of postoperative delirium [46][47][48] . In addition, the use of EEG monitoring also reduce the dosage of general anesthetics, such as volatile agents and propofol [49,50] . Previous studies have reported that excessively exposure to potent volatile agents might increase the incidence of POD [51] .…”
Section: Discussionmentioning
confidence: 99%